Cinnamaldehyde Supplementation Reverts Endothelial Dysfunction in Rat Models of Diet-Induced Obesity: Role of NF-E2-Related Factor-2 - Cristina M. Sena; Ana Pereira; Raquel M. Seiça (Antioxidants, 2022)
Cinnamaldehyde (CN) is an activator of NF-E2-related factor 2 (Nrf2), which has the potential to reduce endothelial dysfunction, oxidative stress and inflammation in metabolic disorders. Our main purpose was to evaluate the effects of CN on vascular dysfunction in metabolic syndrome rats. Normal Wistar (W) rats were divided into eight groups: (1) Wistar (W) rats; (2) W rats fed with a high-fat diet (WHFD); (3) W rats fed with a sucrose diet (WS); (4) WHFD fed with a sucrose diet (WHFDS); (5) W treated with CN (WCn); (6) WS treated with CN (WSCn); (7) WHFD treated with CN (WHFDCn); (8) WHFDS treated with CN (WHFDSCn). CN treatment with 20 mg/kg/day was administered for 8 weeks. Evaluation of metabolic profile, inflammation, endothelial function, oxidative stress, eNOS expression levels and Nrf2 activation was performed. The metabolic dysfunction was greatly exacerbated in the WHFDS rats, accompanied by significantly higher levels of vascular oxidative stress, inflammation, and endothelial dysfunction. In addition, the WHFDS rats displayed significantly reduced activity of Nrf2 at the vascular level. CN significantly reverted endothelial dysfunction in the aortas and the mesenteric arteries. In addition, CN significantly decreased vascular oxidative damage, inflammation at vascular and perivascular level and up-regulated Nrf2 activity in the arteries of WHFDS rats. Cinnamaldehyde, an activator of Nrf2, can be used to improve metabolic profile, and to revert endothelial dysfunction in obesity and metabolic syndrome.